2017
DOI: 10.4314/rejhs.v5i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic leaf extract of <i>Ficus exasperata</i> attenuates Arsenate–mediated hepatic and renal oxidative stress in rats

Abstract: Objective: In furtherance of the scientific search for suitable antidotes for pro-oxidative toxicants which man is exposed to on daily basis, the study investigated the modulatory potential of Ficus exasperata leaf extract on arsenate-mediated hepatic and renal toxicity using rats as a model. Methodology:Twenty-eight rats were sorted into four groups containing seven rats each. Group A (control) received distilled water while 10 mg/kg bw of sodium arsenate was administered intraperitoneally to groups B, C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Simultaneous administrations of propolis and Cd in G4 rats resulted in significant reduction of increased total cholesterol and triglycerides concentrations comparing with corresponding Cd-treated rats (G3). The significant hypercholesterolemia and hyperlipidaemia in the group received the Cd alone are coincided with those reported previously in Cd-treated rats 32,54,55 this is probably associated with biliary obstruction and acute hepatic injury 56 and nephrotic syndrom 57 . The present study revealed that propolis has hypocholesterolemiac and hypolipidaemiac action and alleviated the effect of Cd on lipid profile.…”
Section: Lipid Profile Parameterssupporting
confidence: 74%
“…Simultaneous administrations of propolis and Cd in G4 rats resulted in significant reduction of increased total cholesterol and triglycerides concentrations comparing with corresponding Cd-treated rats (G3). The significant hypercholesterolemia and hyperlipidaemia in the group received the Cd alone are coincided with those reported previously in Cd-treated rats 32,54,55 this is probably associated with biliary obstruction and acute hepatic injury 56 and nephrotic syndrom 57 . The present study revealed that propolis has hypocholesterolemiac and hypolipidaemiac action and alleviated the effect of Cd on lipid profile.…”
Section: Lipid Profile Parameterssupporting
confidence: 74%
“…The current available clinical interventions for the treatment of these NDs are only palliatives with associated adverse effects [ 15 ], thus there is a need for a new, non-invasive, non-toxic and non-expensive treatment for the diseases. Phytochemicals and natural products of plant origin have been considered to have great beneficial effects to human health and help in the prevention and treatment of many diseases including neurodegenerative disorders [ [16] , [17] , [18] ]. Vernonia amygdalina is medicinal plant used traditionally in the treatment and treatment of different diseases [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are known to be the main source of natural antioxidants in the form of phenolic compounds (phenolic acids, flavonoids and polyphenols) ( Table 3 ). Most of the anti-inflammatory, digestive, neuroprotective, hepatoprotective and nephroprotective drugs derived from natural origin have been reported to have antioxidant/radical scavenging mechanism as part of their activity ( Oladele et al., 2020b , c ; Oyewole et al., 2017 ). The ingestion of natural antioxidants has been associated with the reduced risk of cancer, cardiovascular disease, diabetes and other diseases associated with ageing ( Ajayi et al., 2017 ).…”
Section: Medicinal Plants With Pharmacological and Biological Action mentioning
confidence: 99%
“…A vast number of indigenous plants in Nigeria have been reported to reveal antioxidant activity, including Allium sativum, Zingiber officinale, Crocus sativus, Dodonaea viscose, Barlerianoctiflora, Anacardium occidentale, Datura fastuosa, Caesalpiniabonducella and many more as in Table 3 . Several of these antioxidants from plants has been shown to be an active oxygen scavengers or free radicals, with have no any harmful effect on human body ( Oyewole et al., 2017 ; Oladele et al., 2020b , c ; Farombi et al., 2019 ). For detrimental effects of reactive oxygen species to be stopped, plants have shown a powerfully in-built enzymatic and non-enzymatic scavenging capacity.…”
Section: Medicinal Plants With Pharmacological and Biological Action mentioning
confidence: 99%